In vitro plantlet production of the endangered Pinguicula vulgaris - Grevenstuk, Tomás (2015)
This study describes the development of a micropropagation protocol for Pinguicula vulgaris using cultures initiated from in vitro produced seedlings. P. vulgaris is a carnivorous plant with a northern, disjunctly circumpolar distribution and specific habitat requirements, and is hence becoming increasingly rare. Shoot proliferation was significantly influenced by Murashige and Skoog (MS) macronutrient concentration, showing higher proliferation rates in 1/4MS, but was not affected by the addition of 0.1 mg/L 6-benzyladenine (BA) or zeatin (Zea). The best medium for propagating P. vulgaris was plant growth regulator (PGR) free A1/4MS. An average of 7.62 new shoots per initial explant could be obtained after 8 weeks of culture, of which over 79% produced roots during proliferation. Moreover, rooting percentages of 100% were obtained for the initial explants in all the tested media, including media without PGRs. The plantlets were successfully acclimatized to ex vitro conditions, exhibiting normal development.